Takhrij Al Hadis - Muhammad Fikran Said; Abustani Ilyas; Erwin Hafid (CV. SINAR HOWUHOWU, 2026)
Hadith is the second primary source of Islamic teachings after the Qur’an and plays a fundamental role in explaining and detailing Islamic principles. Unlike the Qur’an, however, hadith has not been divinely preserved directly, making its authenticity highly dependent on the process of transmission. This condition led to the emergence of weak and fabricated hadiths from the early period of Islam, necessitating a scientific method to verify and evaluate hadith authenticity. One of the most important methods in hadith studies is takhrij al-hadith, which refers to the process of tracing a hadith back to its original sources by identifying its chains of transmission (sanad), textual content (matan), and various narrations. This study aims to examine the concept of takhrij hadith, its historical development, the reference books used, and the methods of takhrij hadith, particularly manual methods. This research employs a qualitative approach with a library research design by analyzing classical and contemporary hadith literature. The findings reveal that takhrij hadith plays a strategic role in determining the quality of hadith in terms of both sanad and matan and serves as a crucial foundation for preserving the authenticity of hadith as a source of Islamic law. Therefore, mastery of takhrij methods is essential for hadith researchers to ensure scientific and accountable studies.